Nd3+ induced twofold continuous spin reorientation transition and magnetization along the b-axis in a Dy0.9Nd0.1FeO3 single crystal. Issue 14 (20th March 2023) - Shang, Jiamin; Jiang, Jiewen; Zhang, Zhen; Su, Liangbi; Kou, Huamin; Mishina, Elena D.; Pavlov, Victor V.; Barilo, Sergei N.; Shen, Hui; Wu, Anhua
Abstract : An intriguing hybrid magnetic configuration Γ4+3 with non-zero spontaneous magnetization along b -axis was found in DNFO91 single crystal. Contributions of R 3+ were distinguished and the relative strength can be manipulated with magnetic field. Abstract : Rare-earth orthoferrites have attracted intensive attention in the last few years for their abundant physical capabilities. In the present paper, a Nd 3+ doped Dy0.9 Nd0.1 FeO3 (DNFO91) single crystal with high quality was grown by an optical floating zone method, and the magnetic properties have been investigated. We report an intriguing hybrid magnetic configuration Γ4+3 consisting of Γ4 (G x, A y, F z ) and Γ3 (C x, F y, A z ), and it has a non-zero spontaneous magnetic moment along both the b -axis and c -axis. With lowering the temperature, the DNFO91 crystal experiences two continuous spin reorientation transitions from Γ4+3 to Γ2 at 45 K and finally to Γ1 below 43.8 K; here, Γ2 is an incomplete metastable phase transition induced by a magnetic field and disappears at 5000 Oe. Further research directly distinguished the rare-earth ion contributions for the first time, the magnetization along the b -axis originates from Nd 3+ while that along the a -axis comes from Dy 3+, and the relative strength can be further manipulated with an applied magnetic field. An exchange bias behavior was also observed in the M – H curves, revealing the exchange interaction between Dy 3+ /Nd 3+ sublattices and Fe 3+ sublattices. These features of single-crystal DNFO91 can help understand the influence of rare-earth doping on the magnetic structure and physical phenomenon in RFeO3, and this crystal has great application potential.